SIR: a secure and intelligent routing protocol for vehicular ad hoc network. Issue 3 (1st May 2015) - Bhoi, Sourav Kumar; Khilar, Pabitra Mohan
Abstract : Security in routing is an important issue in vehicular ad hoc network (VANET) to protect the valuable information. However, this intelligent transportation system (ITS) services provided by VANET are affected by the malicious vehicles. In this study, a secure and intelligent routing (SIR) protocol is proposed to transmit the data in a quickest path through the authenticated vehicles. Sending the data in a most connected path with less link connection problem enhances the system performance and selecting the authenticated vehicles in this quickest path protects the system from the malicious attacks. In this protocol, a weight W is calculated for every neighbouring junction J neighbour by using the safety message transmission model, delay model, link connectivity model and vehicle position model. The J neighbour with minimum W is selected as the junction through which the data are forwarded to the destination D . Simulation results show SIR performs better than secure path routing protocol, greedy traffic‐aware routing, anchor‐based street and traffic aware routing and geographic source routing protocols in terms of average end‐to‐end delay, network gap encounter and path length.